The Double-Distance of the educator (Palíndromo, 2021)
What motivations and problems arise in the pedagogical practice that trains architects for the future? The article develops a thematic, epistemological and moral approach to analyze the foundations and the repercussions of an aesthetic education project based on an open and experimental episteme guided by a notion of radical naturalism. The need for an amalgam between an ecological conscience and a spiritual conscience is outlined for a full and integral widening of the students' perception.
Keywords: Aesthetic education; Open epistemology; Radical naturalism; Double-distance